2015
DOI: 10.1038/cdd.2014.240
|View full text |Cite
|
Sign up to set email alerts
|

LPS receptor subunits have antagonistic roles in epithelial apoptosis and colonic carcinogenesis

Abstract: Colorectal carcinoma (CRC) is characterized by unlimited proliferation and suppression of apoptosis, selective advantages for tumor survival, and chemoresistance. Lipopolysaccharide (LPS) signaling is involved in both epithelial homeostasis and tumorigenesis, but the relative roles had by LPS receptor subunits CD14 and Toll-like receptor 4 (TLR4) are poorly understood. Our study showed that normal human colonocytes were CD14(+)TLR4(-), whereas cancerous tissues were CD14(+)TLR4(+), by immunofluorescent stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 63 publications
1
67
1
Order By: Relevance
“…In vitro studies have shown a direct effect of LPS via TLR4/MD2 signaling on the stimulation of intestinal epithelial cell proliferation and a resistance to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis (16)(17)(18). Our recent study demonstrated a functional antagonism between CD14 and TLR4 in the regulation of epithelial apoptosis and intestinal carcinogenesis (19). TLR4 counteracted CD14-dependent epithelial apoptosis and promoted survival in developing cancer cells (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro studies have shown a direct effect of LPS via TLR4/MD2 signaling on the stimulation of intestinal epithelial cell proliferation and a resistance to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis (16)(17)(18). Our recent study demonstrated a functional antagonism between CD14 and TLR4 in the regulation of epithelial apoptosis and intestinal carcinogenesis (19). TLR4 counteracted CD14-dependent epithelial apoptosis and promoted survival in developing cancer cells (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Primary antibodies included mouse antihuman PCNA (1:2,000), phospho (p)-and total (t)-IkB (1:2,000), p-and t-ERK1/2 (1:4,000), p-and t-JNK (1:2,000), p-and t-Akt (1:2,000), p-PKCz (Thr410; 1:2,000), p-PKCz (Thr560; 1:5,000; Abcam Epitomics), t-PKCz (1:2,000), p-tyrosine (1:2,000; EMD Millipore), CD14 (1:50 for immunofluorescence and 1:2,000 for Western blot; R&D Systems), TLR4 (1:100 for immunofluorescence and 1:2,000 for Western blot; Santa Cruz Biotechnology), TLR2 (1:2,000; Santa Cruz Biotechnology), MyD88 (1:2,000), bromodeoxyuridine (BrdUrd; 1:200; Abcam), mouse IgG1 and IgG2a isotype controls (R&D Systems), rat IgG2a isotype controls (Abcam), and b-actin (1:10,000; Sigma; refs. 19,31). The secondary antibodies used were goat anti-mouse IgG conjugated to horseradish peroxidase (1:2,000), and to Alexa 594 or 488 (1:1,000; ThermoFisher).…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical imaging technologies used to study organoids include bright-field microscopy, light microscopy, phase microscopy, fluorescence microscopy, confocal microscopy, time-lapse microscopy, multiphoton fluorescence imaging, fluorescence lifetime imaging, and optical coherence tomography (OCT) (8,12,(18)(19)(20)29,30). In wide-field or whole-field microscopy, an entire sample or field of view is illuminated by a light source, and images are captured by a camera.…”
Section: Optical Imaging Of Organoidsmentioning
confidence: 99%